Implementasi Sistem Informasi Manajemen Bengkel Berbasis Web untuk Peningkatan Efisisensi Oprasional (Studi Kasus : Bengkel AA Motor) - Citra Wuladari; Fersellia, Fersellia (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Workshops play an important role in supporting the automotive industry, but many small workshops still use manual recording that is prone to errors and complicates operational management. This study aims to design and implement a web-based information system at the AA Motor Workshop in Kembangkuning Village, Purworejo, to improve work effectiveness. The system was developed using the waterfall method, starting from the needs analysis stage to maintenance. Testing was carried out using the Black Box approach, focusing on the main functions of the system, such as customer management, service, stock, reporting, and user authorization. The test results showed that all modules functioned according to needs and no critical errors were found during testing. The implementation of the system had a significant impact, where work efficiency increased by 84%, data accuracy reached 86%, and the speed of the administration process increased by about 40% compared to the previous manual system. All data is now recorded automatically and can be accessed in real-time via a responsive web dashboard. This study shows that digitalization can improve the performance of small workshops, and the system developed can be used as a model for technology adaptation for similar businesses in rural areas.